FROM LETTER TO PHANTASM. SOME REMARKS ON DELEUZE AND PSYCHOANALYSIS IN LOGIC OF SENSE - MARTA, Claudia (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
From Letter to Phantasm. Some Remarks on Deleuze and Psychoanalysis in Logic of Sense. Our aim is to show how the two heterogeneous series of letter and phantasm make possible, through their convergence understood as the event of sense, a double passage. First, in the order of the Symbolic, the passage of the signifier into the signified. Second, the passage of the whole Symbolic order out of the desiring body. It will be shown that this amounts to a re-conceptualization of causality as sense – event.